The Divine Laws of Charity: The Islamic Solution to Consumerism and Its Consequences - Zin Eddine Dadach (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2020)
In contradiction with the divine laws of charity imposed by Allah (SWT) on the whole universe, money in the social flow of consumerism runs from the poor consumers to the rich companies and banks. The increase of intensity of the natural disasters linked to global warming, could just be a louder global warning from Allah (SWT) through nature in order to urge us to obey the divine laws of charity and change our lifestyle from consumerism to charity-based societies. The recent coronavirus pandemic could also be another global warning from The Merciful (SWT) to force humanity to change the life style based on consumerism. In order to reduce consumerism and its consequences on human health and nature, some people are already adopting â€œminimalistâ€ lifestyles. The most important benefits of this way of life are reducing waste to help the environment, decreasing global carbon dioxide emissions and saving money and time used for excess consumption for charity-based activities.